Guidelines for the standardization of preanalytic variables for blood‐based biomarker studies in Alzheimer's disease research. Issue 5 (30th September 2014) - O'Bryant, Sid E.; Gupta, Veer; Henriksen, Kim; Edwards, Melissa; Jeromin, Andreas; Lista, Simone; Bazenet, Chantal; Soares, Holly; Lovestone, Simon; Hampel, Harald; Montine, Thomas; Blennow, Kaj; et al.
Abstract: The lack of readily available biomarkers is a significant hindrance toward progressing to effective therapeutic and preventative strategies for Alzheimer's disease (AD). Blood‐based biomarkers have potential to overcome access and cost barriers and greatly facilitate advanced neuroimaging and cerebrospinal fluid biomarker approaches. Despite the fact that preanalytical processing is the largest source of variability in laboratory testing, there are no currently available standardized preanalytical guidelines. The current international working group provides the initial starting point for such guidelines for standardized operating procedures (SOPs). It is anticipated that these guidelines will be updated as additional research findings become available. The statement provides (1) a synopsis of selected preanalytical methods utilized in many international AD cohort studies, (2) initial draft guidelines/SOPs for preanalytical methods, and (3) a list of required methodological information and protocols to be made available for publications in the field to foster cross‐validation across cohorts and laboratories.